81.6k views
16 votes
Factorise the following:
x - 14x + 48

User Emad Emami
by
5.5k points

2 Answers

8 votes

Answer:

=−13x+48

Explanation:

Let's simplify step-by-step.

x−14x+48

=x+−14x+48

Combine Like Terms:

=x+−14x+48

=(x+−14x)+(48)

=−13x+48

User Chara
by
4.3k points
4 votes

Answer:

I assume you mean x^2 - 14x + 48. To factor this you want to find a number that adds to -14 and multiplies to 48. That means it'll have to be two negative numbers.

-6*-8 = 48

-6 + (-8) = -14

Your factored expression is (x - 6)(x - 8)

User RompePC
by
5.0k points